Growth processes of an inland Antarctic ice wedge, Mesa Range, northern Victoria Land - Barbara Stenni; Stefano Polesello; Marina Camusso; O. Flora; Rossana Raffi (Annals of Glaciology, 2004)
AbstractDuring the 16th Italian Antarctic Expedition (2000/01) a geomorphological survey of permafrost-related polygons was carried out in the Mesa Range area, upper Rennick Glacier. The investigated site is located in the uppermost reaches of Pain Mesa, which forms the northern sector of the Mesa Range. An ice wedge was found in a volcanic regolith at about 2200ma.s.l. This altitude is below a well-defined erosional trimline, located at about 2380ma.s.l. in this sector of Pain Mesa. The ice was sampled by inserting an ice screw, with an internal diameter of 14 mm, into the ice wedge in vertical sequences. Oriented block samples for thin sections were taken. A co-isotopic study was performed, measuring both oxygen (δ18O) and hydrogen (δD) isotope compositions. Tritium activity was measured, and major cations and anions were determined. The δ18O and δD obtained showed a strong divergence from the snowfalls expected to occur at this elevation, with extremely negative d excess values. Sublimation processes were taken into account to define the origin of the ice forming the wedge. The tritium data obtained suggest that the growth process of the ice wedge might still be active today.